Arshada Nadia wins UMPSA Student Exemplary Award - Naqiah, Puaad (UMPSA, 2024)
KUANTAN, 18 May 2024 - A student of Bachelor of Mechatronic Engineering Technology (Robotics) with Honours, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Arshada Nadia Abdullah, was named the recipient of the Student Exemplary Award at the recent Mercu Sanjung Award Ceremony (MARS).